2012
DOI: 10.1007/s00240-012-0499-6
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plants extracts affect virulence factors expression and biofilm formation by the uropathogenic Escherichia coli

Abstract: Medicinal plants are an important source for the therapeutic remedies of various diseases including urinary tract infections. This prompted us to perform research in this area. We decided to focus on medicinal plants species used in urinary tract infections prevention. The aim of our study was to determine the influence of Betulapendula, Equisetum arvense, Herniaria glabra, Galium odoratum, Urtica dioica, and Vaccinium vitis-idaea extracts on bacterial survival and virulence factors involved in tissue coloniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
2
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 34 publications
7
48
2
7
Order By: Relevance
“…The loss of congo red-binding abilities by the tested rods was observed only at concentrations of 40 and 50 µg/mL of both acids used. We obtained similar results in our previous research (Wojnicz et al, 2012). Results of the current study indicate that AA and UA have relatively similar inhibitory activities on curli fiber synthesis, although it should be noted that AA caused the , 11, 824 5 060, 11, 824, 529, 964 5 060, 11, 824, 529, 964 6 060, 11, 824, 529, 964, 590 6 060, 11, 824, 529, 964, 590 30, 399 4 11, 30, 399, 618 Alpha-hemolysin (n = 11) 0 ---0 - --1 192 2 192, 060 7 192,060,14,419,448,679,964 -4 14, 419, 448, 679 8 14, 419, 448, 679, 060, 192, 590, 964 loss of curli fibers from cell surfaces of 7 strains, while UA caused loss in only 4 cases.…”
Section: Curli Fiber Expressionsupporting
confidence: 92%
See 2 more Smart Citations
“…The loss of congo red-binding abilities by the tested rods was observed only at concentrations of 40 and 50 µg/mL of both acids used. We obtained similar results in our previous research (Wojnicz et al, 2012). Results of the current study indicate that AA and UA have relatively similar inhibitory activities on curli fiber synthesis, although it should be noted that AA caused the , 11, 824 5 060, 11, 824, 529, 964 5 060, 11, 824, 529, 964 6 060, 11, 824, 529, 964, 590 6 060, 11, 824, 529, 964, 590 30, 399 4 11, 30, 399, 618 Alpha-hemolysin (n = 11) 0 ---0 - --1 192 2 192, 060 7 192,060,14,419,448,679,964 -4 14, 419, 448, 679 8 14, 419, 448, 679, 060, 192, 590, 964 loss of curli fibers from cell surfaces of 7 strains, while UA caused loss in only 4 cases.…”
Section: Curli Fiber Expressionsupporting
confidence: 92%
“…The presence of curli fibers coded by this gene allows bacteria to bind to the host cell membrane proteins, colonize the renal tubular epithelium more efficiently, and produce biofilm. The prevalence of the papC gene among clinical isolates collected by us corresponds to results reported earlier (Borisova et al, 2004;Wojnicz et al, 2012). However, the distribution of the hlyA gene found in the current study was higher than reported by Arisoy et al (2008) and Farshad et al (2009).…”
Section: Molecular Characterization Of Bacterial Strainsupporting
confidence: 89%
See 1 more Smart Citation
“…This therapy involves the combination of photosensitizer (PS), light and molecular oxygen (de Melo et al, 2013). In addition, strategies involving nanoparticles (Allaker, 2010; Ramasamy et al, 2016), plant extracts (Wojnicz et al, 2012), and chitosan (Carlson et al, 2008) have been applied against microbial biofilm, with significant results. Further studies are necessary for identifying means to overcome fungal biofilm resistance.…”
Section: Biofilm and Antifungal Resistancementioning
confidence: 99%
“…Rosemary water extracts (RWE1 and RWE2) were prepared from the fresh rosemary leafs collected from Taif and Cairo, respectively, according to the method of Wojnicz et al . (), with some modifications. Rosemary leaves were dried at 37 °C for 48 h (to reach about 9.6% moisture content; dry basis).…”
Section: Methodsmentioning
confidence: 97%